A Change of Heart? Putting gender and transformative thinking at the heart of One CGIAR - Menon-Sen, K.; Stuart, R.; Gordezky, R. (Gender at Work, 2021)
From being a consortium of 15 independent research centres, the CGIAR system is in the process of transitioning to One CGIAR - “a dynamic reformulation of partnerships, knowledge, assets, and global presence, aiming for greater integration and impact”. This consolidation is spurred by the recognition that “delivering science and innovation to advance the transformation of food, land, and water systems in a climate crisis” calls for a “systems transformation approach”. The CGIAR GENDER Platform aims to foster systemic changes in CGIAR centres and create an institutional culture that places gender equality and transformative thinking at the heart of the new One CGIAR agenda. This thinkpiece is an input to the ongoing process of reflection, discussion and dialogue on the strategic possibilities for the GENDER Platform to advance this goal. Our brief was to support the GENDER Platform in making a strong case for “gender at the heart” of One CGIAR, and its own role in this process. Specifically, we were commissioned to prepare a discussion paper with the following elements.  A summary of the current state of thinking and practice on integration of gender concerns into agricultural research and transformation of research institutions to address gender and other exclusionary hierarchies and norms.  An exploration through a feminist lens of challenges and possibilities for gender equality and transformative thinking in One CGIAR.  Strategic possibilities for action.